Keabsahan Pernikahan Perempuan Hamil di Luar Nikah Menurut Hukum Islam dan Legislasi di Indonesia - A. Rahman, Maimun; Lawang, Karimuddin Abdullah (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
Marriage is a sacred bond to build an everlasting household. Regarding the marriage of a woman who is pregnant out of wedlock is a disgrace that some families must cover, so they are looking for a solution by marrying the pregnant woman. However, the problem is the legality of marriage for pregnant women out of wedlock according to Islamic law and Indonesian laws and regulations. This study uses a qualitative research method with a normative juridical approach because it relates to the validity of a law. The results of the study concluded that the marriage of a woman who is pregnant with the man who impregnated her is valid according to Islamic law, even though there are differences of opinion among the Maliki and Hanbali schools of thought that declare it invalid. According to the rules and regulations, it is also stated that it is legal based on KHI article 53, which explains that a woman pregnant out of wedlock can marry the man who made her pregnant.